In/Visibility of Flight Images and narratives of forced migration - Mokre, Monika 1963- (Forced Migration Studies Series, 2024)
In/Visibility is unequally distributed in society and closely related to the distribution of power and privilege. Using images and narratives to mobilize is part of political strategies. The relationship of in/visibility and migration is the guiding question for this edited volume.The chapters discuss multidisciplinary perspectives and factors that contribute to the visibility of forced migration beyond a policy-centered discourse. They focus on the voices and agency of refugees in different countries and contexts. By including research, practical experiences and artistic methods, the volume will be of interest to readers from different academic disciplines and the arts as well as to practitioners